Early fetoscopic tracheal occlusion for extremely severe pulmonary hypoplasia in isolated congenital diaphragmatic hernia: Preliminary results - Ruano, Rodrigo; Peiro, Jose Luis; Silva, Marcos Marques da; Campos, Juliana Alvares Duarte Bonini [UNESP]; Carreras, Elena; Tannuri, Uenis; Zugaib, Marcelo (Wiley, 2013)
Objective: To evaluate the effect of early fetoscopictracheal occlusion (FETO) (22–24 weeks’ gestation) onpulmonary response and neonatal survival in cases ofextremely severe isolated congenital diaphragmatic hernia(CDH). Methods: This was a multicenter study involving fetuseswith extremely severe CDH (lung-to-head ratio < 0.70,liver herniation into the thoracic cavity and no otherdetectable anomalies). Between August 2010 and December 2011, eight fetuses underwent early FETO. Datawere compared with nine fetuses that underwent standard FETO and 10 without fetoscopic procedure fromJanuary 2006 to July 2010. FETO was performed undermaternal epidural anesthesia, supplemented with fetalintramuscular anesthesia. Fetal lung size and vascularitywere evaluated by ultrasound before and every 2 weeksafter FETO. Postnatal therapy was equivalent for bothtreated fetuses and controls. Primary outcome was infantsurvival to 180 days and secondary outcome was fetalpulmonary response. Results: Maternal and fetal demographic characteristicsand obstetric complications were similar in the threegroups (P > 0.05). Infant survival rate was significantlyhigher in the early FETO group (62.5%) comparedwith the standard group (11.1%) and with controls(0%) (P < 0.01). Early FETO resulted in a significantimprovement in fetal lung size and pulmonary vascularitywhen compared with standard FETO (P < 0.01). Conclusions: Early FETO may improve infant survival byfurther increases of lung size and pulmonary vascularityin cases with extremely severe pulmonary hypoplasia inisolated CDH. This study supports formal testing of thehypothesis with a randomized controlled trial.
Keywords: 3D power Doppler; Congenital diaphragmatic hernia; Fetal surgery; Fetal tracheal occlusion; Fetoscopy; Pulmonary hypoplasia; Three-dimensional ultrasonograph